URGENSI PRINSIP GOOD CORPORATE GOVERNANCE DALAM KEGIATAN PERBANKAN SYARIAH - Rizayusmanda, Rizayusmanda (Solusi, 2020)
Islamic banks are financial institutions where products are developed based on the Qur'an, Al-Hadith of the Prophet Muhammad. According to Act Number 21 of 2008 concerning Sharia Banking, Sharia Banks are banks that carry out their business activities based on Sharia Principles, and by type consist of Sharia Commercial Banks and Sharia People Financing Banks. The problem discussed is how is the effort of sharia banking in implementing its business activities based on Article 19 of Law Number 21 Year 2008 concerning Sharia Banking, and whether the application of these business activities requires Good Corporate Governance of sharia banking. This paper is a descriptive normative legal research. Normative legal research is legal research based on secondary data, namely data that has been previously available in the form of legal material. Sharia Banking Efforts in implementing its business activities, namely preparing: Human Resources who are ready to use; organizational structure of the company; division of labor; job duties and authority; and other fields. Then Islamic banking in collaboration with MUI held socialization to the public, and Islamic banking often became a sponsor of religious activities. The principle of Good Corporate Governance (GCG) is a necessity and necessity for sharia banking business activities and sharia business units. This is aimed at the existence of public responsibility related to bank operations so that they truly comply with Islamic banking regulations.